(untitled) (Web of Teachers: Inderscience Research, 2024)
This article discusses the activities of children’s music and art schools in Uzbekistan, focusing on their educational programs, teachers and specialists, creative events, their role in society, and future developments. These schools play a crucial role in educating the younger generation through art and music, helping to develop their social skills and promoting aesthetic education. The article emphasizes the importance of strengthening Uzbekistan’s culture and preparing future generations in the field of art.